Magnetic properties and spin kinetics of a heavy-fermion Kondo lattice - Kochelaev, B.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
A review of peculiarities of magnetic properties and spin kinetics of a heavy-fermion Kondo lattice revealed by electron spin resonance (ESR) experiments and their theoretical analysis is given. Among the issues discussed in some detail are the renormalization of spin kinetics coefficients due to the Kondo effect, formation of the collective spin modes of the Kondo ions and wide-band conduction electrons, unexpected behavior of ESR parameters as functions of temperature and magnetic fields. Special attention is focused on the possible role of the Kondo effect for the ESR signal existence at low temperatures.